A minireplicon of plasmid pBMB26 represents a new typical replicon in the megaplasmids of Bacillus cereus group. (15th December 2017) - Wang, Pengxia; Zhu, Yiguang; Shang, Hui; Deng, Yun; Sun, Ming
Abstract : A new minireplicon ( rep26 minireplicon) from pBMB26, the 188 kb indigenous plasmid related to spore‐crystal association (SCA) phenotype in Bacillus thuringiensis strain YBT‐020, was characterized. A 12 kb Eco RI fragment, which encoded 10 putative open reading frames (ORFs), was capable of supporting replication when cloned in a replication probe vector. Deletion and frame shift mutation analysis showed that a 4.1 kb region encompassing two putative ORFs ( orf21 and orf22 ) was essential for the plasmid replication in B. thuringiensis . Gene orf21 encoding a 49.8 kDa protein (named Rep26) with a helix‐turn‐helix motif showed no homology with known replication proteins and gene orf22 encoding a protein of 82.6 kDa showed homology to bacterial PcrA helicase. The replication origin of rep26 minireplicon was proved to be located in the coding region of orf21 . Plasmid stability experiments indicated that the recombinant plasmid containing rep26 minireplicon has excellent segregational stability. BLASTP analysis revealed that amino acid sequences of ORF21 and ORF22 were well conserved among Bacillus cereus group strains. The rep26 minireplicon was widely distributed and could be defined as a new typical replicon in the megaplasmids of B. cereus group.